Management of double hand amputees with Krukenberg procedure: An option in Nepal - KC, BR; Chand, P; Thapa, BB; Joshi, A (Nepal Orthopaedic Association Journal, 2013)
BACKGROUND : For the last 14 years, Nepal has been struggling with armed conflict in which civilian population have also been the victims- targeted or accidental. Mine blast is the major cause of severe injuries involving multiple systems, bilateral crush injuries of the extremities and severe soft-tissue lacerations. To the victims with bilateral hand amputation or one hand amputation with severely crushed non-functional other hand, rehabilitation and performance regarding activities of daily living (ADL) is a huge problem. Krukenberg procedure, where radius and ulna are separated and a pincer like grasp is created, was considered to restore manual dexterity in this group. METHODS: From August 2001 to April 2007, we carried out the Krukenberg procedure on a group of double hand amputees and single hand amputee with severely crushed or partial amputation of the other hand. The procedure was initially carried out on two double hand amputees to assess the functional result and acceptability by the patient. The procedure was carried out at least 3 months after the amputation in all cases. Post-procedure the patients were rehabilitated by physiotherapist for grip strength and performance of Activities of daily living, ADL (i.e. feeding, personal hygiene, dressing and manual dexterity). RESULTS: Five Krukenberg procedures were performed on three patients: all three were males with mean age of 25 years. Two had double hand amputation and one had single hand amputation with severely crushed other hand with ray amputations. All three patients at three months follow-up could perform ADL by themselves. CONCLUSIONS: The Krukenberg procedure is a surgical option for double hand amputees in a poor country like Nepal. DOI: http://dx.doi.org/10.3126/noaj.v1i1.8130 Nepal Orthopaedic Association Journal Vol.1(1) 2010